Magnetic carrier, two-component developer, and replenishment developer
Patent Information
- Application Number
- JP2021009915
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-25
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-01-25
AI Technical Summary
【0009】 本発明によれば、長期の使用においても磁性キャリア被覆樹脂の損耗が抑制され、安定した画像濃度、トナー飛散の低減を実現する磁性キャリア、及びそれを用いた二成分系現像剤及び補給用現像剤を提供することができる。
Smart Images

Figure 0007652574000018 
Figure 0007652574000019 
Figure 0007652574000020
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic carrier, a two-component developer, and a replenishment developer, which are used in an image forming method for visualizing an electrostatic image by electrophotography. [Background technology]
[0002] Conventionally, in the electrophotographic image forming method, a method is generally used in which an electrostatic latent image is formed on an electrostatic latent image carrier by using various means, and toner is attached to the electrostatic latent image to develop it. In this development, a two-component development method is widely adopted in which carrier particles called magnetic carrier are mixed with the toner, and the toner is triboelectrically charged to give an appropriate amount of positive or negative charge to the toner, and the charge is used as a driving force for development. The two-component development method gives the magnetic carrier the functions of stirring, transporting, and charging the developer. Therefore, the division of functions between the toner and the developer is clear, and the developer performance is easy to control. Here, the magnetic carrier is often composed of a magnetic core that is magnetized to obtain transportability, and a coating resin that coats the magnetic core and provides the ability to impart charge to the toner.
[0003] In recent years, with the advancement of technology in the field of electrophotography, there is a demand for a longer lifespan of the main body, and the magnetic carrier is required to maintain its charge imparting ability even after long-term use. It is known that when used for a long period of time, toner components generally adhere to the surface of the magnetic carrier, and the charge imparting ability of the magnetic carrier decreases due to the decrease in the number of charging sites, resulting in image problems such as changes in color. As a means for achieving the above-mentioned durability against adhesion of toner components (hereinafter also referred to as contamination resistance), an example has been disclosed in which a material with low surface free energy, such as a fluororesin, is used as a coating resin (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 63-235963 [Patent Document 2] JP 2001-66826 A [Patent Document 3] Japanese Patent Application Publication No. 10-55109 Summary of the Invention [Problem to be solved by the invention]
[0005] However, generally, materials with low surface free energy such as fluororesin can suppress adhesion of toner components, but have weak molecular interactions and are easily destroyed by external forces. In addition, materials with low surface free energy such as fluororesin have low adhesion to many other materials and low affinity, making them difficult to mix with. For this reason, when used in combination with a general resin such as acrylic resin, an interface between the components is generated, and peeling between layers starting from the interface is likely to occur. For this reason, when fluororesin is used as the coating resin for the magnetic carrier, the coating resin may be worn or damaged due to mechanical loads generated during stirring or transport in the developing device. As a result of the decrease in surface resistance of the magnetic carrier, the charging ability of the magnetic carrier may decrease (Patent Document 2).
[0006] In order to obtain durability (hereinafter also referred to as wear resistance) against events such as wear or damage of the above-mentioned coating resin layer, it is possible to use a fluorine-modified resin with a trifluoromethyl group bonded to the end. However, it has been found that this structure does not sufficiently reduce the surface free energy of the magnetic carrier surface, resulting in insufficient contamination resistance. On the other hand, when a resin having a fluoroalkyl structure in the side chain is used as a structure for further reducing the surface free energy, the surface free energy between molecules becomes small. As a result, it has been confirmed that the wear resistance becomes insufficient, as in the case of using the above-mentioned fluorine-modified resin (Patent Document 3).
[0007] That is, in order to realize a highly stable magnetic carrier, it is necessary to simultaneously obtain both contamination resistance to suppress adhesion of toner components and wear resistance to suppress wear of the coating resin layer due to mechanical loads and the like. In view of the above, an object of the present invention is to provide a magnetic carrier in which wear of the magnetic carrier coating resin is suppressed even during long-term use, and which realizes stable image density and reduced toner scattering. [Means for solving the problem]
[0008] As a result of extensive investigations, the present inventors have found that by using a magnetic carrier that satisfies specific parameters, it is possible to achieve both excellent contamination resistance and abrasion resistance for the magnetic carrier. According to one aspect of the present invention, there is provided a magnetic carrier including magnetic carrier particles having a magnetic core and a resin coating layer coating a surface of the magnetic core, The resin coating layer contains a resin A having a fluoropolymer portion, The resin coating layer has an average thickness of 50 nm or more, The concentration of nitrogen atoms dN(x), the concentration of silicon atoms dSi(x), the concentration of fluorine atoms dF(x), the concentration of carbon atoms dC(x), the concentration of titanium atoms dTi(x), the concentration of strontium atoms dSr(x), the concentration of tin atoms dSn(x), the concentration of aluminum atoms dAl(x), and the concentration of oxygen atoms detected by X-ray photoelectron spectroscopy at a position of a depth of x nm from the surface of the magnetic carrier particle When F(x) (atomic %) is the ratio (dF(x) / [dN(x)+dSi(x)+dF(x)+dC(x)+dTi(x)+dSr(x)+dSn(x)+dAl(x)+dO(x)]) of the concentration of fluorine atoms dF(x) to the sum of dO(x) (dN(x)+dSi(x)+dF(x)+dC(x)+dTi(x)+dSr(x)+dSn(x)+dAl(x)+dO(x)), F(0) satisfies the following formula (1), F(20) satisfies the following formula (2), When the x is an integer of 0 or more and 20 or less, there is provided a magnetic carrier in which F(x) satisfies the following formula (3) for any x. 5.0≦F(0)≦15 (1) F(20)≦5.0 (2) |F(x+1)-F(x)|≦7.5 (3) According to another aspect of the present invention, there is provided a two-component developer containing the magnetic carrier. According to another aspect of the present invention, there is provided a replenishment developer containing the magnetic carrier. Effect of the Invention
[0009] According to the present invention, it is possible to provide a magnetic carrier in which wear of the magnetic carrier coating resin is suppressed even during long-term use, and which realizes stable image density and reduced toner scattering, and a two-component developer and a replenishment developer using the same. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a schematic diagram of a surface treatment apparatus for performing surface treatment of the toner used in the present invention. [Diagram 2] FIG. 2 is a schematic diagram of an image forming apparatus used in the present invention. [Diagram 3] FIG. 1 is a schematic diagram of a full-color image forming apparatus used in the present invention. [Figure 4] FIG. 2 is a schematic diagram of a resistivity measuring device used in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the present invention, the expressions "xx or more and xx or less" and "xx to xx" expressing a numerical range mean a numerical range including the lower and upper limit endpoints, unless otherwise specified. The magnetic carrier according to the present invention includes magnetic carrier particles having a magnetic core and a resin coating layer that coats the surface of the magnetic core. The resin coating layer contains a resin A having a fluoropolymer moiety, and the resin coating layer has an average thickness of 50 nm or more. Detected by X-ray photoelectron spectroscopy (XPS) at a depth of x nm from the surface of the magnetic carrier particles The concentration of nitrogen atoms is dN(x), the concentration of silicon atoms is dSi(x), The concentration of fluorine atoms is dF(x), the concentration of carbon atoms is dC(x), The concentration of titanium atoms is dTi(x), the concentration of strontium atoms is dSr(x), The sum of the concentration of tin atoms dSn(x), aluminum atoms dAl(x), and oxygen atoms dO(x) (dN(x) + dSi(x) + dF(x) + dC(x) + dTi(x) + dSr(x) + dSn(x) + dAl(x) + dO(x)) The ratio of the fluorine atom concentration dF(x) (dF(x) / [dN(x)+dSi(x)+dF(x)+dC(x)+dTi(x)+dSr(x)+dSn(x)+dAl(x)+dO(x)]) is defined as F(x) (atomic %). At this time, F(0) satisfies the following formula (1), F(20) satisfies the following formula (2), When the x is an integer of 0 to 20, the F(x) satisfies the following formula (3) for any x. 5.0≦F(0)≦15 (1) F(20)≦5.0 (2) |F(x+1)-F(x)|≦7.5 (3)
[0012] The inventors speculate that the reason why satisfying the above requirements suppresses wear of the magnetic carrier coating resin even during long-term use and enables stable image density and reduced toner scattering is as follows. As shown in formula (1), by making the fluorine atom abundance rate in the outermost layer of the magnetic carrier particles 5.0% or more, it is possible to reduce the surface free energy of the magnetic carrier particle surface, which makes it difficult for toner components such as wax to adhere to the magnetic carrier surface, improving contamination resistance. On the other hand, as shown in formula (1), when the fluorine atom abundance rate in the outermost layer of the magnetic carrier particles is 15% or less, the mechanical strength of the outermost surface of the coating resin is improved, and as a result, wear and damage of the coating resin layer is suppressed, and the wear resistance is improved.
[0013] On the other hand, as shown in formula (2), by keeping the atomic fraction of fluorine at a depth of 20 nm below a certain level, it is possible to increase the intermolecular force of the magnetic carrier resin coating layer, thereby improving the abrasion resistance. Furthermore, as shown in formula (3), the fluctuation range of the fluorine atomic fraction in a 1-nm-wide depth direction section is below a certain level, so that no interface between the components exists, which prevents peeling from occurring at the interface and further improves wear resistance. It is therefore presumed that by satisfying all of these formulas (1) to (3), it is possible to achieve both abrasion resistance and stain resistance.
[0014] The resin A is not particularly limited as long as it satisfies the above formulas (1) to (3), and for example, the following can be used: resins consisting of a fluoroalkyl group or a fluoro(poly)ether group (hereinafter sometimes simply referred to as a fluorine-based functional group), or resins such as acrylic resins, urethane resins, polyethylene, polyethylene terephthalate, polystyrene, and phenolic resins partially modified with a fluorine-based functional group, or copolymers or polymer mixtures containing them.
[0015] Moreover, the magnetic carrier according to the present invention preferably satisfies the following requirements. The sum of the concentrations of each atom detected by X-ray photoelectron spectroscopy (XPS) at a position at a depth of x nm from the surface of the magnetic carrier particle For (dN(x)+dSi(x)+dF(x)+dC(x)+dTi(x)+dSr(x)+dSn(x)+dAl(x)+dO(x), When the ratio of the concentration of carbon atoms dC(x) (dC(x) / [dN(x)+dSi(x)+dF(x)+dC(x)+dTi(x)+dSr(x)+dSn(x)+dAl(x)+dO(x)]) is C(x) (atomic %), F(0) / C(0) satisfies the following formula (4), F(20) / C(20) satisfies the following formula (5), When the x is an integer of 0 or more and 20 or less, it is preferable that the F(x) and the C(x) for any x satisfy the following formula (6). 0.060≦F(0) / C(0)≦0.30 (4) F(20) / C(20)≦0.060 (5) |F(x+1) / C(x+1)-F(x) / C(x)|≦0.15···(6)
[0016] As shown in formula (4), the ratio of fluorine atoms to carbon atoms in the outermost layer of the magnetic carrier particles detected by X-ray photoelectron spectroscopy is preferably 0.060 or more. This is because the functional groups derived from fluorine atoms contained in the coating resin contribute to lowering the surface free energy of the magnetic carrier in the vicinity of the surface layer. Furthermore, as shown in formula (4), the ratio is preferably 0.30 or less, since this improves the mechanical strength of the surface of the coating resin layer.
[0017] Furthermore, as shown in formula (5), it is preferable that the ratio of fluorine atoms to carbon atoms detected by X-ray photoelectron spectroscopy is low at a depth of 20 nm from the outermost surface, because this can prevent functional groups derived from fluorine atoms contained in the coating resin from reducing the intermolecular forces between molecules inside the coating resin.
[0018] Furthermore, formula (6) means that the variation width of the atomic ratio of fluorine to carbon atoms in a 1 nm-wide section in the depth direction is below a certain level, which is preferable because it eliminates the interface between components and further improves the wear resistance.
[0019] Moreover, it is preferable that the F(x) satisfies the following formula (7). F(10)≦8.0 (7) That is, this indicates that there are fewer fluorine atoms at a position of 10 nm in the depth direction, which leads to improved wear resistance.
[0020] The content of the resin A in the resin coating layer is preferably 1.0% by mass or more and 50% by mass or less, because the surface free energy of the magnetic carrier particles can be sufficiently reduced by containing the resin A in the coating resin layer at 1.0% by mass or more, and the mechanical strength of the coating resin layer is improved by containing the resin A in the coating resin layer at 50% by mass or less. The resin A preferably has a first repeating structure represented by the following formula (8): The first repeating structure has a fluorine-modified site, and this structure is preferable because it reduces the surface free energy of the coating resin layer and improves the stain resistance.
[0021] [ka]
[0022] In the formula (8), R 1 represents a hydrogen or a methyl group, X 1 stands for COO or O, R 2 represents an alkyl group or a (poly)ether group having 1 to 20 carbon atoms. In the alkyl group or (poly)ether group, some or all of the hydrogen atoms are substituted with fluorine atoms. When some of the hydrogen atoms are substituted with fluorine atoms, some of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms. Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group or (poly)ether group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40 atomic % or less.
[0023] A specific example of the introduction method is to copolymerize an acrylic acid ester or a methacrylic acid ester esterified with a primary alcohol in which some or all of the hydrogen atoms have been substituted with fluorine atoms when polymerizing resin A.
[0024] The proportion of resin A in the coating resin is preferably 1 to 50 parts by mass. If it is more than 1 part by mass, the surface free energy is more likely to decrease, which is preferable because the stain resistance is improved. If it is less than 50 parts by mass, the intermolecular force caused by the low surface free energy of resin A itself can be suppressed, which is preferable because the abrasion resistance is improved. A more preferable range is 3 to 20 parts by mass.
[0025] The first repeating structure preferably has any of the structures represented by the following formulas (8-1) to (8-4) from the viewpoint of achieving both stain resistance and abrasion resistance.
[0026] [ka]
[0027] In the formulas (8-1) to (8-4), R 1 X represents a hydrogen atom or a methyl group. 1 stands for COO or O. 21 R represents a single bond or an alkylene group. 22 Rf represents an alkylene group having a tertiary carbon atom. 11 Rf represents a monovalent group having at least a fluoroalkyl group. 12 Rf represents a fluoroalkyl group having a tertiary or quaternary carbon. 13 represents a perfluoroalkyl group having 4 to 6 carbon atoms. Moreover, it is preferable that the resin A has a second repeating structure represented by the following formula (9), since this will have a greater effect of improving abrasion resistance.
[0028] [ka]
[0029] In formula (9), R 3 R represents H or a methyl group. 4 represents a divalent organic group, and the structure of the divalent organic group is not particularly limited, but for example, structures such as O, COO, and COOY can be used, and Y can have a structure represented by the following formula (Y1).
[0030] [ka]
[0031] In the formula (Y1), Y 1 and Y 2 each independently represents an alkylene group, some of the hydrogen atoms of which may be substituted by a hydroxy group or a halogen; Y 3 represents O or S. In the formula (9), X 2 indicates a polymer having, as a polymerization component, one or more compounds selected from the group consisting of a hydrocarbon group having 1 to 12 carbon atoms, an acrylic acid ester, a methacrylic acid ester, styrene, and acrylonitrile.
[0032] In the resin A, when the mass of the resin A in the coating resin is X, the mass of the first repeating structure is a, and the mass of the second repeating structure is b, the larger the value of R expressed by the following formula, the greater the effect of improving abrasion resistance can be obtained. R = b / (Xa) The R refers to the proportion of the second repeating unit in the portion excluding the first repeating unit in resin A. If the value of R is 0.5 or more, the effect of improving abrasion resistance can be significantly obtained, which is preferable, and further, it is particularly preferable that the value of R is 0.95 or more.
[0033] The resin A may have a functional group such as a nitrogen-containing group, a carboxyl group, or a hydroxyl group. By having these, it is possible to suppress the charge-up of the developer, especially in a low humidity environment. In addition, by having a hydroxyl value, the effect of hydrogen bonding is also exhibited, so that the wear resistance is further improved, which is preferable. When a carboxyl group is used, the acid value of the resin A is preferably in the range of 5 to 100 mgKOH / mg. When it is 5 or more, the charge-up is improved, and when it is 100 or less, the charge retention of the developer is improved. When a hydroxyl group is used, the hydroxyl value of the resin A is preferably in the range of 5 to 50 mgKOH / mg. When it is 5 or more, the charge-up is improved, and when it is 50 or less, the charge retention of the developer is improved. It is preferable that the coating resin layer contains a resin B having a third repeating structure represented by the following formula (10), since this further improves the abrasion resistance.
[0034] [ka]
[0035] In the formula (10), R 5 represents hydrogen or a methyl group, and R 6 represents a hydrocarbon group having 1 to 12 carbon atoms. Specific examples of the introduction method include copolymerizing the following monomers when polymerizing resin B: methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, decyl acrylate, dodecyl acrylate, cyclobutyl acrylate, cyclohexyl acrylate, cyclopentyl acrylate, cyclooctyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, dodecyl methacrylate, cyclobutyl methacrylate, cyclohexyl methacrylate, cyclopentyl methacrylate, and cyclooctyl methacrylate.
[0036] In the resin B, when the SP value of the second repeating structure is SPa2 and the SP value of the third repeating structure is SPb3, it is preferable that the SPa2 and SPb3 satisfy the following formula. |SPa2-SPb3|≦2.5 By satisfying this relational formula, the compatibility with the resin A and the resin B is increased, and the abrasion resistance is improved, which is preferable. The smaller the value of |SPa2-SPb3|, the stronger the intermolecular force acting between the second repeating structure and the third repeating structure, and the greater the effect of improving abrasion resistance can be obtained. As the third repeating structure, only one type of structure may be contained, or two or more types may be contained.
[0037] The content of resin B is preferably as large as possible within the range satisfying the above formulas (1) to (3) since a greater effect of improving abrasion resistance can be obtained. In particular, the content of resin B is preferably 50% by mass or more, and more preferably 90% by mass or more, based on the total coating resin.
[0038] In the formula (10), R 6 By containing an alicyclic hydrocarbon group, the surface (coating surface) of the resin coating layer that coats the surface of the magnetic core becomes smooth, and adhesion of toner-derived components such as toner and external additives that impart fluidity to the toner can be suppressed. Furthermore, the alicyclic hydrocarbon is preferable because it suppresses aggregation of the fluorine-based functional groups in Resin A and plays a role in assisting the orientation of the fluorine-based functional groups on the surface, thereby further improving the contamination resistance.
[0039] The acid value of the resin B is preferably 0 mgKOH / g or more and 3.0 mgKOH / g or less, more preferably 0 mgKOH / g or more and 2.8 mgKOH / g or less, and even more preferably 0 mgKOH / g or more and 2.5 mgKOH / g or less. If the acid value of the resin B is 3.0 mgKOH / g or less, the self-aggregation of the resin due to the influence of the acid value is unlikely to occur, and the smoothness of the surface (coating surface) of the resin coating layer is unlikely to decrease. The acid value of the resin B can be controlled by using a monomer having a polar group such as a carboxy group or a sulfo group (sulfonic acid group) during the synthesis of the resin B and adjusting the amount of the monomer added. However, since a low acid value is preferable, it is preferable not to use a monomer having a polar group. Even when a resin is synthesized using only a monomer that forms an ester bond, a slight acid value may occur in the synthesized resin. This is thought to be because a part of the ester bond is decomposed during the synthesis (polymerization) of the resin to generate a carboxyl group.
[0040] The average thickness of the coating resin layer containing the resin A and the resin B is preferably 50 nm or more and 3000 nm or less, from the viewpoint of achieving both durability and electrical resistance. The resin coating layer of the present invention preferably contains conductive fine particles in the coating resin. The conductive fine particles can appropriately control the resistivity of the electrophotographic magnetic carrier. As a result, the counter charge after the toner is developed can be released and white spots can be suppressed. The content of the conductive fine particles added to the coating resin is preferably 0.1 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the coating resin. If it is less than 0.1 parts by mass, it is difficult to obtain the effect of adding the conductive fine particles, and if it exceeds 20 parts by mass, there is a concern that the color will decrease due to the detachment of the conductive fine particles. Examples of the conductive fine particles include carbon black, titanium oxide, and silver.
[0041] In addition, the coating resin may contain fine particles for the purpose of increasing the ability to impart charge to the toner and improving the releasability. The fine particles contained in the resin coating layer may be fine particles of either organic or inorganic materials, but crosslinked resin fine particles or inorganic fine particles having the strength to maintain the shape of the fine particles when coated are preferred. Examples of crosslinked resins forming crosslinked resin fine particles include crosslinked polymethyl methacrylate resins, crosslinked polystyrene resins, melamine resins, guanamine resins, urea resins, phenolic resins, and nylon resins. Examples of inorganic fine particles include silica, alumina, titania, etc. The content of the fine particles in the resin coating layer is 0.1 parts by mass per 100 parts by mass of the coating resin. It is preferable that the content is from 1 part by mass to 20 parts by mass.
[0042] <Magnetic core manufacturing method> As the magnetic core according to the present invention, known magnetic particles such as magnetite particles, ferrite particles, magnetic material-dispersed resin particles, etc. can be used. Among them, magnetic particles obtained by filling the pores of porous magnetic particles with resin or magnetic material-dispersed resin particles, i.e., magnetic particles containing a magnetic oxide and a resin composition, are preferred from the viewpoint of reducing the specific gravity of the magnetic carrier and extending its life.
[0043] Reducing the specific gravity of the magnetic carrier reduces the load on the toner in the developer state in the developing device, prevents the adhesion of toner components to the magnetic carrier surface, reduces the load on the magnetic carriers themselves, and further suppresses wear and damage to the resin coating layer. It also improves dot reproducibility, making it possible to obtain high-definition images.
[0044] In addition, the resin contained in the pores of the porous magnetic particles can be a copolymer resin used as a coating resin, but is not limited to this and can be any known resin. As the thermoplastic resin, the copolymer used as the coating resin is preferable, but other examples include the following. Polystyrene, polymethyl methacrylate, styrene-acrylic acid ester copolymer, styrene-methacrylic acid ester copolymer, styrene-butadiene copolymer, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinyl acetate, polyvinylidene fluoride resin, fluorocarbon resin, perfluorocarbon resin, solvent-soluble perfluorocarbon resin, polyvinylpyrrolidone, petroleum resin, novolac resin, saturated alkyl polyester resin, polyethylene terephthalate, polybutylene terephthalate, aromatic polyester resin such as polyarylate, polyamide resin, polyacetal resin, polycarbonate resin, polyethersulfone resin, polysulfone resin, polyphenylene sulfide resin, polyether ketone resin.
[0045] Examples of thermosetting resins include the following: phenol resins, modified phenol resins, maleic resins, alkyd resins, epoxy resins, acrylic resins, unsaturated polyesters obtained by polycondensation of maleic anhydride, terephthalic acid, and polyhydric alcohols, urea resins, melamine resins, urea-melamine resins, xylene resins, toluene resins, guanamine resins, melamine-guanamine resins, acetoguanamine resins, glyptal resins, furan resins, silicone resins, polyimides, polyamideimide resins, polyetherimide resins, and polyurethane resins.
[0046] As a method for filling the voids of the ferrite particles having a porous shape with a resin component, there is a method of diluting the resin component in a solvent and adding the diluted solution to the porous magnetic core particles. The solvent used here may be any solvent capable of dissolving each resin component. In the case of a resin soluble in an organic solvent, an organic solvent such as toluene, xylene, cellosolve butyl acetate, methyl ethyl ketone, methyl isobutyl ketone, or methanol may be used. In the case of a water-soluble resin component or an emulsion-type resin component, water may be used. As a method for adding a resin component diluted with a solvent to the inside of the porous magnetic core particles, there is a method of impregnating the resin component by a coating method such as a dipping method, a spraying method, a brush coating method, a fluidized bed method, or a kneading method, and then volatilizing the solvent. In the case of filling with a thermosetting resin, after volatilizing the solvent, the temperature is raised to the temperature at which the resin used hardens, and a hardening reaction is carried out.
[0047] On the other hand, specific methods for producing magnetic material-dispersed resin particles include the following. For example, submicron magnetic materials such as iron powder, magnetite particles, and ferrite particles are kneaded so as to disperse them in a thermoplastic resin, pulverized to a desired magnetic carrier particle size, and, if necessary, subjected to a thermal or mechanical spheroidizing treatment to obtain the particles. It is also possible to produce the magnetic material-dispersed resin particles by dispersing the magnetic material in a monomer and polymerizing the monomer to form a resin.
[0048] In this case, the resin may be a vinyl resin, a polyester resin, an epoxy resin, a phenol resin, a urea resin, a polyurethane resin, a polyimide resin, a cellulose resin, a silicone resin, an acrylic resin, or a polyether resin. The resin may be one type or a mixture of two or more types. In particular, a phenol resin is preferable in that it increases the strength of the magnetic core. The true density and resistivity can be adjusted by adjusting the amount of the magnetic material. Specifically, in the case of magnetic particles, it is preferable to add 70% by mass or more and 95% by mass or less to the magnetic carrier.
[0049] The magnetic core preferably has a volume average particle size (D50) of 20 μm to 80 μm in order to enable the coating resin to be uniformly coated, prevent magnetic carrier adhesion, and ensure an appropriate density of the developer magnetic brush to obtain high quality images. The resistivity of the magnetic core is 1.0×10 at an electric field strength of 1000 (V / cm). 5 (Ω cm) or more 1.0×10 14 (Ω·cm) or less is preferable because good developability can be obtained.
[0050] The method of coating the magnetic core surface with the coating resin is not particularly limited, and can be performed by a known method. For example, there is a so-called immersion method in which the magnetic core and the coating resin solution are stirred while volatilizing the solvent, and the coating resin is coated on the magnetic core surface. Specific examples include a universal mixer (manufactured by Fuji Paudal Co., Ltd.) and a Nauta Mixer (manufactured by Hosokawa Micron Co., Ltd.). There is also a method in which the coating resin solution is sprayed from a spray nozzle while forming a fluidized bed, and the coating resin is coated on the magnetic core surface. Specific examples include a Spiracoater (manufactured by Okada Seiko Co., Ltd.) and a Spiraflow (manufactured by Freund Corporation). There is also a method in which the coating resin is coated on the magnetic core in the form of particles in a dry manner. Specific examples include a treatment method using an apparatus such as a Hybridizer (manufactured by Nara Machinery Co., Ltd.), Mechanofusion (manufactured by Hosokawa Micron Co., Ltd.), HighFlex Gral (manufactured by Fukae Powtec Co., Ltd.), and Theta Composer (manufactured by Tokuju Kogyo Co., Ltd.). Next, the magnetic carrier will be described.
[0051] <Magnetic carrier> The magnetic carrier has a magnetization strength of 40 (Am 2 / kg) or more 80(Am 2 / kg) or less. When the magnetization strength of the magnetic carrier is within the above range, the magnetic binding force to the developing sleeve is appropriate, so that the occurrence of magnetic carrier adhesion can be suppressed more effectively. In addition, the stress applied to the toner in the magnetic brush can be reduced, so that the deterioration of the toner and adhesion to other members can be suppressed more effectively.
[0052] The strength of magnetization of the magnetic carrier can be adjusted by the amount of resin contained. The residual magnetization of the magnetic carrier is 20.0 (Am 2 / kg) or less, and 10.0 (Am 2 When the residual magnetization of the magnetic carrier is within the above range, particularly good fluidity is obtained as a developer, and good dot reproducibility is obtained.
[0053] The magnetic carrier has a true density of 2.5 (g / cm 3 ) or more 5.5 (g / cm 3 ) or less, and 3.0 (g / cm 3 ) or more 5.0 (g / cm 3 ) or less. A two-component developer containing a magnetic carrier having a true density in this range exerts a small load on the toner, and adhesion of the toner components to the magnetic carrier is suppressed. In order to achieve both good developability at low electric field strength and prevention of magnetic carrier adhesion, a true density in this range is also preferable for the magnetic carrier.
[0054] The magnetic carrier preferably has a volume average particle diameter (D50) of 21 μm or more and 81 μm or less, because it is excellent in terms of the ability to charge the toner, the suppression of magnetic carrier adhesion to the image area, and the improvement of image quality, and more preferably has a volume average particle diameter (D50) of 25 μm or more and 60 μm or less. Next, the preferred toner constitution for achieving the object of the present invention will be described in detail below.
[0055] <Binding resin> The toner particles in the present invention may use the following polymers as the binder resin. Homopolymers of styrene and its substitutes, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-based copolymers, such as styrene-p-chlorostyrene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-acrylic acid ester copolymer, and styrene-methacrylic acid ester copolymer; styrene-based copolymer resin, polyester resin, a mixture of polyester resin and vinyl resin, or a hybrid resin in which both are partially reacted; polyvinyl chloride, phenol resin, naturally modified phenol resin, naturally modified maleic acid resin, acrylic resin, methacrylic resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane, polyamide resin, furan resin, epoxy resin, xylene resin, polyethylene resin, and polypropylene resin. Among them, polyester resin is preferably used as the main component because excellent low-temperature fixability can be obtained.
[0056] As the monomers used in the polyester unit of the polyester resin, polyhydric alcohols (divalent or trivalent or higher alcohols), polyvalent carboxylic acids (divalent or trivalent or higher carboxylic acids), their acid anhydrides or their lower alkyl esters are used. Here, in order to produce a branched polymer in order to express "strain hardening", it is effective to partially crosslink the amorphous resin molecule, and for this purpose, it is preferable to use a polyfunctional compound having a valence of three or more. Therefore, it is preferable to include a trivalent or higher carboxylic acid, its acid anhydride or its lower alkyl ester, and / or a trivalent or higher alcohol as the raw material monomer of the polyester unit.
[0057] As the polyhydric alcohol monomer used in the polyester unit of the polyester resin, the following polyhydric alcohol monomers can be used. Examples of the dihydric alcohol component include ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, hydrogenated bisphenol A, bisphenol represented by formula (A) and its derivatives; and diols represented by formula (B).
[0058] [ka]
[0059] (In the formula, R is an ethylene or propylene group, x and y are each an integer of 0 or more, and the average value of x+y is 0 or more and 10 or less.)
[0060] [ka]
[0061] Examples of trihydric or higher alcohol components include the following: sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene. Of these, glycerol, trimethylolpropane, and pentaerythritol are preferably used. These dihydric alcohols and trihydric or higher alcohols can be used alone or in combination.
[0062] As the polybasic carboxylic acid monomer used in the polyester unit of the polyester resin, the following polybasic carboxylic acid monomers can be used. Examples of divalent carboxylic acid components include the following: maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctylsuccinic acid, isooctylsuccinic acid, anhydrides of these acids, and lower alkyl esters thereof. Of these, maleic acid, fumaric acid, terephthalic acid, and n-dodecenylsuccinic acid are preferably used.
[0063] Examples of trivalent or higher carboxylic acids, their acid anhydrides or their lower alkyl esters include the following. 1,2,4-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, their acid anhydrides or their lower alkyl esters. Among these, 1,2,4-benzenetricarboxylic acid, i.e., trimellitic acid or its derivatives, is particularly preferred because it is inexpensive and easy to control the reaction. These divalent carboxylic acids and trivalent or higher carboxylic acids can be used alone or in combination.
[0064] The method for producing the polyester unit of the present invention is not particularly limited, and a known method can be used. For example, the above-mentioned alcohol monomer and carboxylic acid monomer are simultaneously added, and polymerized through an esterification reaction or an ester exchange reaction and a condensation reaction to produce a polyester resin. The polymerization temperature is not particularly limited, but is preferably in the range of 180°C to 290°C. When polymerizing the polyester unit, for example, a polymerization catalyst such as a titanium-based catalyst, a tin-based catalyst, zinc acetate, antimony trioxide, or germanium dioxide can be used. In particular, the binder resin of the present invention is more preferably a polyester unit polymerized using a tin-based catalyst.
[0065] The polyester resin preferably has an acid value of 5 mgKOH / g or more and 20 mgKOH / g or less, and a hydroxyl value of 20 mgKOH / g or more and 70 mgKOH / g or less, because this reduces the amount of moisture adsorbed in a high-temperature and high-humidity environment, keeps the anti-electrostatic adhesion low, and provides excellent fogging resistance.
[0066] The binder resin may be a mixture of a low molecular weight resin and a high molecular weight resin. The content ratio of the high molecular weight resin to the low molecular weight resin is preferably 40 / 60 or more and 85 / 15 or less by mass, because this provides excellent low temperature fixing property and hot offset resistance.
[0067] <Release agent> Examples of waxes that can be used in the toner of the present invention include the following: hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes containing fatty acid esters as the main component such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax. Further examples include the following. Saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and parinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene bi Saturated fatty acid bisamides such as stearic acid amide; unsaturated fatty acid amides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N' dioleyl adipic acid amide, and N,N' dioleyl sebacic acid amide; aromatic bisamides such as m-xylene bisstearic acid amide and N,N' distearyl isophthalic acid amide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols, such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats.
[0068] Among these waxes, from the viewpoint of improving low-temperature fixing property and fixing separation property, preferred are hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax. In the present invention, the hydrocarbon waxes are more preferred from the viewpoint of further improving hot offset resistance.
[0069] In the present invention, the wax is preferably used in an amount of 3 parts by mass or more and 8 parts by mass or less per 100 parts by mass of the binder resin. In addition, in an endothermic curve during temperature rise measured by a differential scanning calorimetry (DSC) device, the peak temperature of the maximum endothermic peak of the wax is preferably 45° C. or more and 140° C. or less. If the peak temperature of the maximum endothermic peak of the wax is within the above range, the toner can have both excellent storage stability and excellent hot offset resistance, which is preferable.
[0070] <Coloring agent> The toner particles in the present invention may contain a colorant. Examples of the colorant include the following. Examples of black colorants include carbon black, yellow colorants, magenta colorants, and cyan colorants used to tone the color to black. Although a pigment may be used alone as the colorant, it is more preferable to use a dye and a pigment in combination to improve the clarity of the colorant from the viewpoint of image quality of a full-color image.
[0071] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.
[0072] Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.
[0073] Pigments for cyan toners include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45; copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. Dyes for cyan toners include CI Solvent Blue 70.
[0074] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162.
[0075] These colorants can be used alone or in combination, or in the form of a solid solution. The colorant is selected in consideration of hue angle, chroma, brightness, light resistance, transparency on an OHP sheet, and dispersibility in a toner. The content of the colorant is preferably 0.1 parts by mass or more and 30.0 parts by mass or less based on the total amount of the resin components.
[0076] <Inorganic fine particles> The toner preferably contains inorganic fine particles for the main purpose of improving fluidity and chargeability, and the inorganic fine particles are preferably attached to the toner surface. As inorganic fine particles serving as spacer particles for improving the releasability between the toner and the magnetic carrier, silica particles having a maximum peak particle size based on the number distribution of 80 nm to 200 nm are preferred, and in order to function as spacer particles while better suppressing detachment from the toner, a particle size of 100 nm to 150 nm is more preferred.
[0077] In order to improve the fluidity of the toner, it is preferable to contain inorganic fine particles having a maximum peak particle size based on the number distribution of 20 nm to 50 nm, and it is also preferable to use them in combination with the silica particles. Further, in order to improve the fluidity and transferability, other external additives may be added to the toner particles. The external additive added to the surface of the toner particles preferably contains inorganic fine particles such as titanium oxide, alumina oxide, and silica, and a plurality of types may be used in combination.
[0078] The total content of the external additives is preferably 0.3 parts by mass to 5.0 parts by mass, more preferably 0.8 parts by mass to 4.0 parts by mass, based on 100 parts by mass of toner particles. Among them, the content of silica particles having a maximum peak particle size of 80 nm to 200 nm based on the number distribution standard is preferably 0.1 parts by mass to 2.5 parts by mass, more preferably 0.5 parts by mass to 2.0 parts by mass. Within this range, the effect as a spacer particle is more remarkable.
[0079] The surfaces of silica particles or inorganic fine particles used as external additives are preferably subjected to a hydrophobic treatment, which is preferably carried out with coupling agents such as various titanium coupling agents and silane coupling agents, fatty acids and their metal salts, silicone oils, or combinations thereof.
[0080] Examples of titanium coupling agents include the following: tetrabutyl titanate, tetraoctyl titanate, isopropyl triisostearoyl titanate, isopropyl tridecylbenzenesulfonyl titanate, and bis(dioctyl pyrophosphate)oxyacetate titanate.
[0081] Examples of silane coupling agents include the following: γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, N-β-(N-vinylbenzylaminoethyl)γ-aminopropyltrimethoxysilane hydrochloride, hexamethyldisilazane, methyltrimethoxysilane, butyltrimethoxysilane, isobutyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, phenyltrimethoxysilane, o-methylphenyltrimethoxysilane, and p-methylphenyltrimethoxysilane.
[0082] Examples of fatty acids include the following: long-chain fatty acids such as undecylic acid, lauric acid, tridecylic acid, dodecylic acid, myristic acid, palmitic acid, pentadecylic acid, stearic acid, heptadecylic acid, arachidic acid, montanic acid, oleic acid, linoleic acid, and arachidonic acid. Examples of metals in the fatty acid metal salts include zinc, iron, magnesium, aluminum, calcium, sodium, and lithium.
[0083] Examples of silicone oils include dimethyl silicone oil, methylphenyl silicone oil, and amino-modified silicone oil. The hydrophobic treatment is preferably carried out by adding a hydrophobic treatment agent to the particles to be treated in an amount of 1% by mass or more and 30% by mass or less (more preferably 3% by mass or more and 7% by mass or less) relative to the particles to be treated, thereby coating the particles to be treated.
[0084] The degree of hydrophobization of the hydrophobized external additive is not particularly limited, but for example, the hydrophobization degree after the treatment is preferably from 40 to 98. The hydrophobization degree indicates the wettability of a sample with respect to methanol, and is an index of hydrophobicity. When the toner of the present invention is mixed with a magnetic carrier to be used as a two-component developer, good results are usually obtained when the mixing ratio of the magnetic carrier is 2% by mass or more and 15% by mass or less, preferably 4% by mass or more and 13% by mass or less, in terms of the toner concentration in the developer. If the toner concentration is less than 2% by mass, the image density tends to decrease, and if it exceeds 15% by mass, fogging and scattering in the machine tend to occur.
[0085] In addition, in a replenishing developer to be replenished to a developing device in response to a decrease in the toner concentration of the two-component developer in the developing device, the amount of toner is 2 parts by mass or more and 50 parts by mass or less per part by mass of the replenishing magnetic carrier. Next, an image forming apparatus equipped with a developing device using the magnetic carrier, two-component developer and replenishment developer of the present invention will be described by way of example, but the developing device used in the developing method of the present invention is not limited to this.
[0086] <Image forming method> 2, the electrostatic latent image carrier 1 rotates in the direction of the arrow (counterclockwise direction) in the figure. The electrostatic latent image carrier 1 is charged by a charger 2, which is a charging means (charging step), and an electrostatic latent image is formed on the surface of the charged electrostatic latent image carrier 1 by exposure by an exposure device 3, which is an electrostatic latent image forming means (electrostatic latent image forming step). The developing device 4 has a developing container 5 that contains a two-component developer, and a developer carrier 6 is arranged in a rotatable state, and a magnet 7 is contained inside the developer carrier 6 as a magnetic field generating means. At least one of the magnets 7 is installed so as to face the latent image carrier. The two-component developer is held on the developer carrier 6 by the magnetic field of the magnet 7, and the amount of the two-component developer is regulated by a regulating member 8, and the developer is transported to a developing section that faces the electrostatic latent image carrier 1. In the developing section, a magnetic brush is formed by the magnetic field generated by the magnet 7. Thereafter, a developing bias consisting of an alternating electric field superimposed on a direct current electric field is applied, and the electrostatic latent image is visualized as a toner image (developing process). The toner image formed on the electrostatic latent image carrier 1 is electrostatically transferred to a recording medium (transfer material) 12 by a transfer charger 11 (transfer process).
[0087] Here, as shown in FIG. 3, the image may be temporarily transferred from the electrostatic latent image carrier 1 to an intermediate transfer body 9, and then electrostatically transferred to a recording medium 12 as a transfer material (transfer step).
[0088] Thereafter, the recording medium 12 is conveyed to a fixing device 13, where the toner is fixed onto the recording medium 12 by applying heat and pressure (fixing step). Thereafter, the recording medium 12 is discharged outside the apparatus as an output image. After the transfer process, the toner remaining on the electrostatic latent image carrier 1 is removed by a cleaner 15. Thereafter, the electrostatic latent image carrier 1 cleaned by the cleaner 15 is electrically initialized by light irradiation from a pre-exposure means 16, and the above image forming operation is repeated.
[0089] FIG. 3 is a schematic diagram showing an example of the image forming method of the present invention applied to a full-color image forming apparatus. The arrangement of the image forming units K, Y, C, M, and arrows indicating the directions of rotation are not limited to those shown in the figure, and K stands for black, Y for yellow, C for cyan, and M for magenta.
[0090] In FIG. 3, electrostatic latent image carriers 1K, 1Y, 1C, and 1M rotate in the direction of the arrow (clockwise direction). Each electrostatic latent image carrier is charged by chargers 2K, 2Y, 2C, and 2M, which are charging means (charging process). An electrostatic latent image is formed on the charged surface of each electrostatic latent image carrier by exposure by exposure devices 3K, 3Y, 3C, and 3M, which are electrostatic latent image forming means (electrostatic latent image forming process). After that, the electrostatic latent image is visualized as a toner image by a two-component developer carried on developer carriers 6K, 6Y, 6C, and 6M provided in developing devices 4K, 4Y, 4C, and 4M, which are developing means (developing process). The electrostatic latent image is then transferred to an intermediate transfer body 9 by intermediate transfer chargers 10K, 10Y, 10C, and 10M, which are transfer means. The image is then transferred to a recording medium 12 by a transfer charger 11, which is transfer means (transfer process). The recording medium 12 is heated and pressure-fixed by a fixing device 13, which is a fixing means (fixing step), and is output as an image.
[0091] The intermediate transfer body cleaner 14, which is a cleaning member for the intermediate transfer body 9, collects the residual toner and the like. Specifically, the development method of the present invention is preferably performed by applying an AC voltage to the developer carrier to form an alternating electric field in the development area while the magnetic brush is in contact with the photosensitive body. The distance (SD distance) between the developer carrier (developing sleeve) 6 and the photosensitive drum is 100 μm or more and 1000 μm or less, which is good for suppressing magnetic carrier adhesion and improving dot reproducibility. If it is narrower than 100 μm, the supply of developer is likely to be insufficient, resulting in low image density. If it exceeds 1000 μm, the magnetic field lines from the magnetic pole S1 will spread and the density of the magnetic brush will decrease, causing events such as a decrease in dot reproducibility and magnetic carrier flying to the photosensitive body due to a weakening of the force binding the magnetic carrier, which will cause a decrease in image quality and a decrease in parts life.
[0092] The voltage (Vpp) between the peaks of the alternating electric field is 300 V or more and 3000 V or less, preferably 500 V or more and 1800 V or less. Also, the frequency is 500 Hz or more and 10,000 Hz or less, preferably 1000 or more and 7000 Hz or less, and each can be appropriately selected and used according to the process. In this case, examples of the waveform of the AC bias for forming the alternating electric field include a triangular wave, a rectangular wave, a sine wave, or a waveform with a changed duty ratio. Sometimes, in order to cope with changes in the formation speed of the toner image, it is preferable to perform development by applying a developing bias voltage (intermittent alternating superimposed voltage) having a discontinuous AC bias voltage to the developer carrier. If the applied voltage is lower than 300 V, it is difficult to obtain sufficient image density, and there may be cases where the fogged toner in the non-image area cannot be recovered well. Also, when it exceeds 3000 V, the latent image may be disturbed through the magnetic brush, leading to image quality degradation.
[0093] By using a two-component developer having well-charged toner, the fogging voltage (Vback) can be lowered, and since the primary charging of the photoreceptor can be reduced, the life of the photoreceptor can be extended. Vback depends on the developing system but is 200 V or less, more preferably 150 V or less. As the contrast potential, 100 V or more and 400 V or less is preferably used so that sufficient image density can be obtained.
[0094] Also, when the frequency is lower than 500 Hz, although it is related to the process speed, as the configuration of the electrostatic latent image-bearing photoreceptor, it can usually be the same as the photoreceptor used in an image forming apparatus. For example, a photoreceptor having a configuration in which a conductive layer, an undercoat layer, a charge generation layer, a charge transport layer, and, if necessary, a charge injection layer are provided in this order on a conductive substrate such as aluminum or SUS can be mentioned. The conductive layer, the undercoat layer, the charge generation layer, and the charge transport layer can usually be those used for a photoreceptor. As the outermost surface layer of the photoreceptor, for example, a charge injection layer or a protective layer may be used.
[0095] <Method for Measuring Si Atom Concentration by XPS> The magnetic carrier is attached onto the indium foil. At that time, the particles are attached evenly so that the indium foil is not exposed. The measurement conditions are as follows. Equipment: PHI5000VERSAPROBEII (ULVAC-PHI, Inc.) Irradiation: AlKα ray Output: 25W 15kV Photoelectron capture angle: 45° PassEnergy: 58.7eV Step size: 0.125eV XPS peaks: C1s, O1s, Si2p, Ti2p, Sr3d Gun type: GCIB Time: 75 min Interval: 1.5 minutes Sputter Setting: 5kV
[0096] As shown in these conditions, when the interval is set to 1.5 min, elemental analysis can be performed in the depth direction of about 1.0 nm, making it possible to perform analysis every 1.0 nm in depth up to 20 nm.
[0097] <Method for measuring the volume average particle size (D50) of magnetic carriers and porous magnetic cores> The particle size distribution was measured using a laser diffraction / scattering particle size distribution measuring device "Microtrac MT3300EX" (manufactured by Nikkiso Co., Ltd.). The volume average particle size (D50) of the magnetic carrier and porous magnetic core was measured using a sample supply device for dry measurements, the "One-Shot Dry Type Sample Conditioner Turbotrac" (manufactured by Nikkiso Co., Ltd.). The supply conditions for the Turbotrac were a dust collector used as the reduced pressure source, with an air volume of approximately 33 L / sec and a pressure of approximately 17 kPa. Control was performed automatically on the software. The particle size was calculated as the 50% particle size (D50), which is the cumulative value of the volume average. Control and analysis were performed using the attached software (version 10.3.3-202D). The measurement conditions were as follows: SetZero time: 10 seconds Measurement time: 10 seconds Number of measurements: 1 Particle refractive index: 1.81% Particle shape: non-spherical Measurement upper limit: 1408μm Measurement lower limit: 0.243μm Measurement environment: Temperature 23℃, relative humidity 50%
[0098] <Measurement of pore size and pore volume of porous magnetic core> The pore size distribution of the porous magnetic core is measured by mercury intrusion porosimetry. The measurement principle is as follows. In this measurement, the pressure applied to the mercury is changed and the amount of mercury that penetrates into the pores is measured. The conditions under which mercury can penetrate into the pores can be expressed from the balance of forces as PD=-4σCOSθ, where P is the pressure, D is the pore diameter, and θ and σ are the contact angle and surface tension of the mercury, respectively. If the contact angle and surface tension are constants, then the pressure P is inversely proportional to the pore diameter D into which mercury can penetrate at that time. For this reason, the pressure P and the amount of penetrating liquid V at that time are measured by changing the pressure, and the horizontal axis P of the PV curve is directly substituted into the pore diameter from this equation to determine the pore distribution.
[0099] Measurements can be performed using a measuring device such as the fully automatic multi-function mercury porosimeter PoreMaster series / PoreMaster-GT series manufactured by Yuasa Ionics Co., Ltd. or the automatic porosimeter Autopore IV9500 series manufactured by Shimadzu Corporation. Specifically, the measurements were performed using an Autopore IV9520 from Shimadzu Corporation under the following conditions and procedures. Measurement conditions Measurement environment: 20℃ Measurement cell sample volume: 5cm 3 , Press-in volume: 1.1cm 3 , Application: For powder Measurement range: 2.0 psia (13.8 kPa) to 59989.6 psia (413.6 MPa) Measurement steps: 80 steps (When the pore diameter is taken logarithmically, the steps are spaced at equal intervals.) Pressurization parameters Exhaust pressure: 50μmHg Exhaust time: 5.0 min Mercury injection pressure: 2.0 psia (13.8 kPa) Equilibrium time: 5secs High pressure parameter equilibration time: 5secs Mercury parameters Advancing contact angle: 130.0 degrees Receding contact angle: 130.0degrees Surface tension: 485.0mN / m (485.0dynes / cm) Mercury density: 13.5335g / mL
[0100] Measurement procedure (1) Approximately 1.0 g of the porous magnetic core is weighed and placed in the sample cell. Enter the weighing value. (2) In the low pressure section, measure the range from 2.0 psia (13.8 kPa) to 45.8 psia (315.6 kPa). (3) In the high-pressure section, the range was measured to be between 45.9 psia (316.3 kPa) and 59,989.6 psia (413.6 MPa). (4) The pore size distribution is calculated from the mercury injection pressure and the amount of mercury injected.
[0101] (2), (3), and (4) were performed automatically using the software provided with the device. From the pore size distribution measured as described above, the pore size at which the differential pore volume is maximum in the pore size range of 0.1 μm or more and 3.0 μm or less is read, and this is taken as the pore size at which the differential pore volume is maximum. In addition, the pore volume obtained by integrating the differential pore volume in the pore diameter range of 0.1 μm to 3.0 μm was calculated using the attached software.
[0102] <Measuring method of weight average particle size (D4) and number average particle size (D1)> The weight average particle diameter (D4) and number average particle diameter (D1) of the toner were measured using CDA-1000X (manufactured by Sysmex Corporation).
[0103] <Powder X-ray diffraction analysis> The XRD pattern was measured using an X-ray diffraction analyzer (X'pertPRO-MPD: manufactured by PANalytical). X-rays were generated at an accelerating voltage of 45 kV and a current of 40 mA. The powder X-ray measurement conditions were as follows. Divergence slit: 1 / 4rad (fixed) Anti-scatter slit: 1 / 2rad Soller slit: 0.04rad Mask: 15mm Anti-scatter slit: 7.5mm Spinner: Yes Measurement method Scan axis: Continuous 2θ / θ Measurement range: 5.0°≦2θ≦80° Step interval: 0.026deg / s Scan speed: 0.525deg / s
[0104] <Method of measuring the magnetization strength of a magnetic core> The magnetization strength of the magnetic core can be measured using a vibrating sample magnetometer or a direct current magnetization characteristic recorder (BH tracer). In the examples described below, the magnetization strength is measured using a vibrating sample magnetometer BHV-30 (manufactured by Riken Denshi Co., Ltd.) in the following manner.
[0105] A cylindrical plastic container is filled with magnetic cores sufficiently densely to prepare a sample. The actual mass of the sample packed in the container is measured. After that, the sample is attached in the plastic container with instant adhesive so that it does not move. Using a standard sample, the external magnetic field axis and the magnetization moment axis are calibrated at 5000 / 4π (kA / m). The magnetization strength was measured from the loop of the magnetization moment when an external magnetic field of 5000 / 4π (kA / m) was applied at a sweep speed of 5 (min / roop). From this, the magnetization strength of the magnetic core (Am 2 / kg).
[0106] <Measurement of the average thickness of the resin coating layer> The average thickness of the resin coating layer was measured by observing the cross section of the magnetic carrier with a transmission electron microscope (TEM) (50,000x magnification). Specifically, the magnetic carrier was subjected to ion milling using an argon ion milling device (Hitachi High-Technologies Corporation, product name E-3500), and the thickness of the resin coating layer on the cross section of the magnetic carrier was measured at any five points per particle using a transmission electron microscope (TEM) (50,000x magnification). The same measurement as above was carried out for 10 magnetic carrier particles, and the average of 50 measured values of the thickness of the resin coating layer obtained was taken as the average layer thickness. The ion milling measurement conditions were as follows: Beam diameter: 400μm (half width) Ion gun acceleration voltage: 5kV Ion gun discharge voltage: 4kV Ion gun discharge current: 463μA Ion gun irradiation current: 90μA / cm3 / 1min
[0107] <Toner manufacturing method> The method for producing toner particles is not particularly limited, but a pulverization method is preferred because it is easy to disperse a release agent or a polymer in which a styrene-acrylic polymer is graft-polymerized onto a polyolefin. The reason for this is that when toner particles are produced in an aqueous medium, a release agent having high hydrophobicity or a polymer in which a styrene-acrylic polymer is graft-polymerized onto a polyolefin tends to be localized inside the toner particles. This makes it difficult to form a core-shell structure using the above-mentioned heat treatment device. The procedure for producing the toner by the pulverization method will be described below.
[0108] In the raw material mixing process, materials constituting the toner particles, such as binder resin, release agent, colorant, crystalline polyester, and other components such as charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include double con mixers, V-type mixers, drum mixers, super mixers, Henschel mixers, Nauta mixers, and Mechano Hybrids (manufactured by Nippon Coke & Engineering Co., Ltd.).
[0109] Next, the mixed materials are melt-kneaded to disperse the wax in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of continuous production. For example, a KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with a two-roller or the like, and cooled with water or the like in a cooling process.
[0110] The cooled resin composition is then pulverized to a desired particle size in a pulverization step, for example by coarse pulverization using a pulverizer, and then further pulverized to a desired particle size in a fine pulverizer. Examples of the pulverizer include a crusher, a hammer mill, a feather mill, etc. Examples of the fine pulverizer include a Cryptron System (manufactured by Kawasaki Heavy Industries, Ltd.), a Super Rotor (manufactured by Nisshin Engineering Co., Ltd.), a Turbo Mill (manufactured by Turbo Kogyo Co., Ltd.), and a fine pulverizer using an air jet system.
[0111] Thereafter, the mixture is classified as necessary using a classifier or sieve separator, such as the inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), the centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), TSP Separator (manufactured by Hosokawa Micron Corporation), or Faculty (manufactured by Hosokawa Micron Corporation).
[0112] Thereafter, the toner particles are surface-treated by heating to increase the circularity of the toner. For example, the surface treatment can be performed by using the surface treatment device shown in FIG. The mixture supplied by the material supply means 1 is introduced into an introduction pipe 3, which is installed vertically to the material supply means, by compressed gas adjusted by a compressed gas adjustment means 2. The mixture passing through the introduction pipe 3 is uniformly dispersed by a conical protruding member 4 installed in the center of the material supply means, and is introduced into eight supply pipes 5 that radiate outward, and then into a treatment chamber 6 where heat treatment is carried out.
[0113] At this time, the flow of the mixture supplied to the treatment chamber is regulated by a regulating means 9 for regulating the flow of the mixture provided in the treatment chamber. Therefore, the mixture supplied to the treatment chamber is heat-treated while swirling in the treatment chamber, and then cooled. Hot air for heat-treating the supplied mixture is supplied from hot air supplying means 7, and is introduced into the treatment chamber by spirally swirling the hot air using a swirling member 13 for swirling the hot air. In terms of the configuration, the swirling member 13 for swirling the hot air has a plurality of blades, and the swirling of the hot air can be controlled by the number and angle of the blades. The hot air supplied into the treatment chamber preferably has a temperature of 100°C to 300°C at the outlet of the hot air supplying means 7. If the temperature at the outlet of the hot air supplying means is within the above range, it is possible to uniformly spheronize the toner particles while suppressing fusion and coalescence of the toner particles caused by overheating the mixture.
[0114] The heat-treated toner particles are then cooled by cold air supplied from cold air supplying means 8. The temperature of the cold air supplied from cold air supplying means 8 is preferably -20°C to 30°C. If the temperature of the cold air is within the above range, the heat-treated toner particles can be efficiently cooled, and the fusion and coalescence of the heat-treated toner particles can be suppressed without impeding the uniform spheroidization of the mixture. The absolute moisture content of the cold air is 0.5 g / m 3 More than 15.0g / m 3 It is preferable that:
[0115] Next, the cooled heat-treated toner particles are collected by the collecting means 10 at the bottom end of the processing chamber. A blower (not shown) is provided ahead of the collecting means, so that the toner particles are sucked and transported by the blower. In addition, the powder particle supply port 14 is provided so that the swirling direction of the supplied mixture and the swirling direction of the hot air are the same, and the recovery means 10 of the surface treatment device is provided on the outer periphery of the treatment chamber so as to maintain the swirling direction of the swirled powder particles. Furthermore, the cold air supplied from the cold air supply means 8 is configured to be supplied from the outer periphery of the device to the circumferential surface inside the treatment chamber in a horizontal and tangential direction. The swirling direction of the toner particles supplied from the powder particle supply port 14, the swirling direction of the cold air supplied from the cold air supply means 8, and the swirling direction of the hot air supplied from the hot air supply means 7 are all the same direction. Therefore, no turbulence occurs inside the treatment chamber 6, the swirling flow inside the device is strengthened, a strong centrifugal force is applied to the toner particles, and the dispersibility of the toner particles is further improved, so that toner particles with a uniform shape and few coalesced particles can be obtained.
[0116] It is preferable that the average circularity of the toner is 0.960 or more and 0.980 or less, since the non-electrostatic adhesion can be suppressed to a low level and excellent fogging resistance can be obtained. Then, the fine powder side is divided into two parts, one for fine powder and the other for coarse powder. For example, an inertial classification system, Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), is used to divide the particles into two parts. A desired amount of silica fine particles A is externally added to the surface of each of the two heat-treated toner particles. As a method for externally adding the particles, a method of stirring and mixing using a mixer as an external adder can be mentioned. Examples of mixing equipment include a double cone mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.), and a Nobilta (manufactured by Hosokawa Micron Corporation). In this case, if necessary, an external additive other than the silica fine particles, such as a fluidizing agent, may be added to the mixture. The methods for measuring various physical properties of the toner and raw materials are described below.
[0117] <Measurement of the peak molecular weight and weight average molecular weight of a polymer in which a styrene-acrylic polymer is graft-polymerized onto a binder resin and polyolefin by GPC> The molecular weight distribution of the THF-soluble component of the resin is measured by gel permeation chromatography (GPC) as follows. First, dissolve the toner in tetrahydrofuran (THF) over 24 hours at room temperature. Then, filter the resulting solution through a solvent-resistant membrane filter "MAESORIDISC" with a pore size of 0.2 μm (manufactured by Tosoh Corporation) to obtain a sample solution. The sample solution is adjusted so that the concentration of the components soluble in THF is about 0.8% by mass. Using this sample solution, measurements are performed under the following conditions. Apparatus: HLC8120GPC (Detector: RI) (manufactured by Tosoh Corporation) Column: 7 columns of Shodex KF-801, 802, 803, 804, 805, 806, 807 (manufactured by Showa Denko KK) Eluent: Tetrahydrofuran (THF) Flow rate: 1.0 mL / min Oven temperature: 40.0 °C Sample injection volume: 0.10 mL
[0118] When calculating the molecular weight of the sample, a molecular weight calibration curve prepared using a standard polystyrene resin is used. Examples of the standard polystyrene resin include the following. Product name "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation
[0119] <Measurement of the specific resistance of the magnetic carrier> Using the measuring device shown in Figure 4, measure the specific resistance value of the magnetic carrier. The resistivity is measured by filling the cell E with magnetic carrier particles 1, arranging a lower electrode 41 and an upper electrode 42 so as to be in contact with the magnetic carrier particles 1, applying a voltage between these electrodes, and measuring the current that flows at that time to obtain the resistivity. The conditions for measuring the resistivity are: contact area S between the filled magnetic carrier and the electrodes = approx. 2.4 cm 2 The sample thickness d is approximately 0.2 cm, and the load on the upper electrode is 240 g. Voltage is applied in the order of conditions (I), (II), and (III), and the current at the applied voltage under condition (III) is measured. The sample thickness d is then accurately measured, and the resistivity (Ω·cm) at each electric field strength (V / cm) is calculated, and the resistivity at an electric field strength of 3000 V / cm is taken as the resistivity of the sample's magnetic carrier.
[0120] Application conditions (I): (Change from 0V to 1000V: Increase in steps of 200V every 30 seconds) (II): (1000V hold for 30 seconds) (III): (Change from 1000V to 0V: Decrease in steps of 200V every 30 seconds) Magnetic carrier resistivity (Ω cm) = (applied voltage (V) / measured current (A)) × S (cm 2 ) / d(cm) Electric field strength (V / cm) = applied voltage (V) / d (cm) EXAMPLES
[0121] <Production example of porous magnetic core particles> Process 1 (weighing and mixing process) Fe2O3: 61.7% by mass MnCO3: 34.2% by mass Mg(OH)2: 3.0% by mass SrCO3: 1.1% by mass The ferrite raw material was weighed out so as to obtain the above-mentioned mass percentage. Thereafter, the mixture was ground and mixed for 2 hours in a dry ball mill using zirconia balls (diameter 10 mm).
[0122] Step 2 (pre-firing step) After crushing and mixing, the mixture was sintered in air at 950℃ for 2 hours in a burner-type sintering furnace to produce calcined ferrite. The composition of the ferrite is as follows: (MnO) a (MgO) b (SrO) c (Fe2O3) d In the above formula, a = 0.40, b = 0.07, c = 0.01, d = 0.52
[0123] Process 3 (Crushing process) After crushing to about 0.5 mm with a crusher, 30 parts by mass of water was added to 100 parts by mass of the calcined ferrite and crushed in a wet ball mill using zirconia balls (diameter 1.0 mm) for 2 hours. After separating the balls, the mixture was crushed in a wet bead mill using zirconia beads (diameter 1.0 mm) for 3 hours to obtain a ferrite slurry.
[0124] Process 4 (granulation process) To the ferrite slurry, 2.0 parts by mass of polyvinyl alcohol per 100 parts by mass of the calcined ferrite was added as a binder, and the mixture was granulated into spherical particles having a volume average particle size of 40 μm using a spray dryer (manufacturer: Okawara Kakoki).
[0125] Step 5 (Main firing step) In order to control the firing atmosphere, firing was performed in an electric furnace under a nitrogen atmosphere (oxygen concentration: 1.0% by volume) at 1150° C. for 4 hours.
[0126] Step 6 (sorting step) The aggregated particles were disintegrated, and then sieved through a sieve with 250 μm openings to remove coarse particles, to obtain porous magnetic core particles, designated as magnetic core 1. The physical properties of the obtained magnetic core 1 are shown in Table 1.
[0127] Process 7 (resin filling process) 100.0 parts by mass of magnetic core 1 was placed in the stirring vessel of a mixer (Dalton's universal stirrer NDMV type). Then, while maintaining the temperature at 60°C, nitrogen was introduced while reducing the pressure to 2.3 kPa, and the silicone resin solution was dropped under reduced pressure so that the silicone resin component was 7.5 parts by mass relative to the magnetic core 1, and stirring was continued for 2 hours after the end of the dropwise addition. Thereafter, the temperature was raised to 70°C, the solvent was removed under reduced pressure, and the silicone resin composition obtained from the silicone resin solution was filled into the particles of the magnetic core 1. After cooling, the obtained filled core particles were transferred to a mixer (Sugiyama Heavy Industries' drum mixer UD-AT type) having a spiral blade in a rotatable mixing vessel, and the temperature was raised to 220°C at a heating rate of 2 (°C / min) under nitrogen atmosphere and normal pressure. Heating and stirring were performed at this temperature for 60 minutes to harden the resin. After heat treatment, low magnetic products were separated by magnetic separation and classified with a sieve with an opening of 150 μm to obtain magnetic core 2. The physical properties of the obtained magnetic core 2 are shown in Table 1.
[0128] <Production example of ferrite core particles> Process 1 (weighing and mixing process) Fe2O3: 61.7% by mass MnCO3: 34.2% by mass Mg(OH)2: 3.0% by mass SrCO3: 1.1% by mass The ferrite raw material was weighed out so as to obtain the above-mentioned mass percentage. Thereafter, the mixture was ground and mixed for 2 hours in a dry ball mill using zirconia balls (diameter 10 mm).
[0129] Step 2 (pre-firing step) After crushing and mixing, the mixture was sintered in air at 1000℃ for 2 hours in a burner-type sintering furnace to produce calcined ferrite. The composition of the ferrite is as follows: (MnO) a (MgO) b (SrO) c (Fe2O3) d In the above formula, a = 0.40, b = 0.07, c = 0.01, d = 0.52
[0130] Process 3 (Crushing process) After crushing to about 0.5 mm with a crusher, 30 parts by mass of water was added to 100 parts by mass of the calcined ferrite and crushed in a wet ball mill using stainless steel balls (diameter 1.0 mm) for 2 hours. After separating the balls, the mixture was crushed in a wet bead mill using stainless steel balls (diameter 1.0 mm) for 3 hours to obtain a ferrite slurry.
[0131] Process 4 (granulation process) To the ferrite slurry, 2.0 parts by mass of polyvinyl alcohol per 100 parts by mass of the calcined ferrite was added as a binder, and the mixture was granulated into spherical particles having a volume average particle size of 45 μm using a spray dryer (manufacturer: Okawara Kakoki).
[0132] Step 5 (Main firing step) In order to control the firing atmosphere, firing was performed in an electric furnace under a nitrogen atmosphere (oxygen concentration: 0.6% by volume) at 1200° C. for 6 hours.
[0133] Step 6 (sorting step) After the aggregated particles were crushed, the mixture was sieved through a sieve with an opening of 250 μm to remove coarse particles, thereby obtaining ferrite core particles, which are designated as magnetic cores 3. The physical properties of the obtained magnetic core 3 are shown in Table 1.
[0134] <Production example of magnetic material-dispersed resin core particles> Magnetite fine particles (spherical, number-average particle size 250 nm) and a silane coupling agent (3-(2-aminoethylaminopropyl)trimethoxysilane) (3.0% by mass relative to the mass of the magnetite fine particles) were introduced into a vessel. Then, the magnetite fine particles were surface-treated by high-speed mixing and stirring at a temperature of 100°C or higher in the vessel.
[0135] Phenol 10 parts by weight Formaldehyde solution (37% by weight aqueous formaldehyde solution) 16 parts by weight Surface-treated magnetite particles: 84 parts by mass The above materials were introduced into a reaction vessel and mixed thoroughly at a temperature of 40°C. Then, the mixture was heated to 85°C with an average heating rate of 3°C / min while stirring, and 4 parts by mass of 28% ammonia water and 25 parts by mass of water were added to the reactor. The mixture was kept at 85°C and polymerized for 3 hours to harden. The peripheral speed of the stirring blade was 1.8 m / sec.
[0136] After the polymerization reaction, the mixture was cooled to 30°C and water was added. The supernatant was removed to obtain a precipitate, which was washed with water and then air-dried. The air-dried product was dried at 60°C under reduced pressure (5 hPa or less) to obtain magnetic material-dispersed resin core particles. These are designated as magnetic cores 4. The physical properties of the obtained magnetic core 4 are shown in Table 1.
[0137] [Table 1]
[0138] <Method of manufacturing resin A1> A fluorine-containing acrylic monomer corresponding to the first partial structure (first repeat structure) and a monomer corresponding to the second partial structure (second repeat structure) were added to a four-neck flask equipped with a reflux condenser, a thermometer, a nitrogen suction tube, and a ground-wheel type stirrer. The structures of the first partial structure and the second partial structure, and the amounts of the monomers added are shown in Table 2A.
[0139] Further, 100 parts by mass of toluene, 100 parts by mass of methyl ethyl ketone, and 2.0 parts by mass of azobisisovaleronitrile were added. The obtained mixture was kept at 70°C for 10 hours under a nitrogen gas flow, and after the polymerization reaction was completed, washing was repeated to obtain a resin A1 solution (solid content 35% by mass). The value of SPa2 is shown in Table 2A.
[0140] <Method of Manufacturing Resins A2 to A9> Resins A2 to A9 were obtained in the same manner as in the production method for Resin A1, except that the structures of the first and second partial structures and the amounts of the monomers added were changed as shown in Table 2A. The values of SPa2 are shown in Table 2A. R in the first substructure (first repeat structure) 2 the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group or (poly)ether group in The atomic ratio of fluorine atoms and the ratio of halogen atoms other than fluorine atoms are shown in Table 2B.
[0141] [Table 2A]
[0142] [Table 2B]
[0143] <How to prepare macromonomer> The macromonomer used in Resin B can be synthesized, for example, by the following method. The raw materials shown below were added to a four-neck flask equipped with a reflux condenser, thermometer, nitrogen inlet, and ground-type stirrer. Methacrylic acid chloride: 1.7% by mass Polymethyl methacrylate with a hydroxyl group at one end (Mw: approx. 5000) ··· 98.3% by mass Further, 100 parts by mass of THF and 1.0 part by mass of 4-tert-butylcatechol were added, and the mixture was heated under reflux for 5 hours under a nitrogen stream. After completion of the reaction, the mixture was washed with sodium hydrogen carbonate to obtain a macromonomer solution.
[0144] <Method of manufacturing resin B1> The monomers indicated below and the macromonomer were added to a four-neck flask equipped with a reflux condenser, thermometer, nitrogen inlet, and ground-gear stirrer. Cyclohexyl methacrylate: 74.5% by mass Methyl methacrylate: 0.5% by mass Methacrylic acid macromonomer: 25.0% by mass Further, 100 parts by mass of toluene, 100 parts by mass of methyl ethyl ketone, and 2.0 parts by mass of azobisisovaleronitrile were added. The obtained mixture was kept at 70°C for 10 hours under a nitrogen stream, and after the polymerization reaction was completed, washing was repeated to obtain a resin B1 solution (solid content 35% by mass). The weight average molecular weight of this solution by gel permeation chromatography (GPC) was 57,000. The SPb3 value was 10.6.
[0145] <Method of manufacturing resin B2> The monomers indicated below and the macromonomer were added to a four-neck flask equipped with a reflux condenser, thermometer, nitrogen inlet, and ground-gear stirrer. Methyl methacrylate: 75% by mass Methacrylic acid macromonomer: 25% by mass Further, 100 parts by mass of toluene, 100 parts by mass of methyl ethyl ketone, and 2.0 parts by mass of azobisisovaleronitrile were added. The obtained mixture was kept at 70°C for 10 hours under a nitrogen stream, and after the polymerization reaction was completed, washing was repeated to obtain a resin B2 solution (solid content 35% by mass). The weight average molecular weight of this solution by gel permeation chromatography (GPC) was 35,000. The SPb3 value was 9.91.
[0146] <Method of manufacturing resin B3> The monomers indicated below and the macromonomer were added to a four-neck flask equipped with a reflux condenser, thermometer, nitrogen inlet, and ground-gear stirrer. Cyclohexyl acrylate: 75% by mass Methacrylic acid macromonomer: 25% by mass Further, 100 parts by mass of toluene, 100 parts by mass of methyl ethyl ketone, and 2.0 parts by mass of azobisisovaleronitrile were added. The obtained mixture was kept at 70°C for 10 hours under a nitrogen stream, and after the polymerization reaction was completed, washing was repeated to obtain a resin B3 solution (solid content 35% by mass). The weight average molecular weight of this solution by gel permeation chromatography (GPC) was 55,000. The SPb3 value was 11.5.
[0147] <Method of manufacturing resin B4> 50 parts of xylene was placed in an autoclave, and after replacing with nitrogen, the temperature was raised to 185°C in a sealed state with stirring. A mixed solution of 100 parts of styrene, 50 parts of di-t-butyl peroxide, and 50 parts of xylene was continuously dropped for 3 hours while controlling the temperature inside the autoclave at 185°C, and polymerization was carried out. The same temperature was maintained for another 1 hour to complete the polymerization, and a resin B4 solution (solid content 50% by mass) was obtained. The weight average molecular weight of this solution measured by gel permeation chromatography (GPC) was 5,000.
[0148] <Resin coating process> How to make magnetic carrier 1 Using the magnetic core 3 shown in Table 1, a resin solution having the composition shown in Table 3 was added to a planetary motion mixer maintained at a reduced pressure (1.5 kPa) and a temperature of 60° C., so that the resin component solid content was 2.0 parts by mass per 100 parts by mass of the magnetic core. A Nauta Mixer VN type manufactured by Hosokawa Micron Corporation was used as the planetary motion mixer. The resin solution was poured in by pouring in 1 / 3 of the volume, and the solvent was removed and the coating was performed for 20 minutes, followed by another 1 / 3 of the volume, the solvent was removed and the coating was performed for 20 minutes, and then another 1 / 3 of the volume was poured in, and the solvent was removed and the coating was performed for 20 minutes.
[0149] The magnetic carrier coated with the coating resin composition was then transferred to a mixer (a UD-AT type drum mixer manufactured by Sugiyama Heavy Industries Co., Ltd.) having a spiral blade in a rotatable mixing container. The mixture was heat-treated for 2 hours at 120°C in a nitrogen atmosphere while stirring at 10 revolutions per minute. The magnetic carrier 1 obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 150 μm, and then classified by an air classifier. Magnetic carrier 1 having a volume distribution standard 50% particle size (D50) of 39.1 μm was obtained. The analytical results of the obtained magnetic carrier 1 are shown in Table 4.
[0150] ·How to prepare magnetic carriers 2-18 Magnetic Carriers 2 to 18 were obtained in the same manner as in the production method of Magnetic Carrier 1, except that the resin and magnetic core added were changed as shown in Table 3. The analysis results are shown in Table 4.
[0151] -How to make magnetic carrier 19 Magnetic carrier 19 was obtained in the same manner as magnetic carrier 1, except that the resin solution was added in an amount of 1.0 part by mass in terms of the solid content of the resin component per 100 parts by mass of the magnetic core. The analysis results are shown in Table 4.
[0152] Method for producing magnetic carrier 20 Magnetic carrier 20 was obtained in the same manner as magnetic carrier 1, except that the resin solution was added in an amount of 0.5 parts by mass as the solid content of the resin component per 100 parts by mass of the magnetic core. The analysis results are shown in Table 4.
[0153] ·Method of manufacturing magnetic carrier 21 Magnetic carrier 21 was obtained in the same manner as magnetic carrier 18, except that the resin solution was added in an amount of 1.9 parts by mass as the solid content of the resin component per 100 parts by mass of the magnetic core. The analysis results are shown in Table 4.
[0154] Method for producing the magnetic carrier 22 100 parts by mass of magnetic carrier 21 and 0.1 parts by mass of polytetrafluoroethylene resin fine particles (PTFE, TLP10F-1 (manufactured by Mitsui DuPont Fluorochemicals Co., Ltd.) were added to Nobilta (manufactured by Hosokawa Micron Corporation). Then, as a preliminary mixing step, the mixture was stirred and mixed for 2 minutes at a peripheral speed of the outermost end of the stirring member of 1 m / sec, and then, while adjusting the peripheral speed of the outermost end of the stirring member to 10 m / sec, a coating treatment was performed for 15 minutes to obtain magnetic carrier particles. The obtained magnetic carrier particles were separated into low magnetic particles by magnetic separation, passed through a sieve with an opening of 150 μm, and then classified with an air classifier to obtain magnetic carrier 22 having a 50% particle size (D50) of 40.8 μm based on volume distribution. The analysis results are shown in Table 4.
[0155] [Table 3]
[0156] [Table 4]
[0157] <Toner 1 Manufacturing Example> Polyester resin 100 parts Fischer-Tropsch wax (maximum endothermic peak temperature 90°C) 4 parts 0.3 parts of 3,5-di-t-butylsalicylic acid aluminum compound (Bontron E88, manufactured by Orient Chemical Industry Co., Ltd.) Carbon black 10 parts The above materials were mixed using a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 1500 rpm for a rotation time of 5 min, and then kneaded using a twin-screw kneader (PCM-30, manufactured by Ikegai Co., Ltd.) set at a temperature of 130°C. The kneaded product obtained was cooled and coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. The coarsely crushed product obtained was finely crushed using a mechanical crusher (T-250, manufactured by Turbo Kogyo Co., Ltd.). Further, classification was performed using a Faculty (F-300, manufactured by Hosokawa Micron Corporation), and toner base particles 1 were obtained. The operating conditions were a classification rotor rotation speed of 11000 rpm and a dispersion rotor rotation speed of 7200 rpm.
[0158] Toner base particles 1 100 parts Silica fine particles A (number average particle size (D1) is 120 nm) 2.0 parts The raw materials shown in the above recipe were mixed using a Henschel mixer (FM-10C type, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 1900 rpm for a rotation time of 3 minutes, and then heat-treated using the surface treatment device shown in Figure 1 to obtain heat-treated toner particles 1. The operating conditions were feed rate = 5 kg / hr, hot air temperature C = 160°C, and hot air flow rate = 6 m 3 / min., cold air temperature E=-5℃, cold air flow rate=4m 3 / min., Blower air volume = 20m 3 / min., Injection air flow rate = 1m 3 / min. The obtained heat-treated toner particles were classified by an inertial classification system using an Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.) to obtain heat-treated toner particles.
[0159] Heat-treated toner particles 1 100 parts Silica fine particles B (number average particle size (D1) is 20 nm) 0.6 parts The above materials were mixed in a Henschel mixer (FM-75, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotation speed of 1900 rpm for a rotation time of 3 minutes to obtain Toner 1.
[0160] <Example 1> 9 parts by mass of toner 1 was added to 91 parts by mass of magnetic carrier 1, and the mixture was shaken with a shaker (YS-8D type: manufactured by Yayoi Co., Ltd.) to prepare 300 g of a two-component developer. The vibration conditions of the shaker were 150 rpm and 2 minutes. On the other hand, 90 parts by mass of toner 1 was added to 10 parts by mass of magnetic carrier 1, and mixed for 5 minutes in a V-type mixer in an environment of normal temperature and humidity (temperature 23° C. / relative humidity 50%) to obtain a replenishment developer. The following evaluations were carried out using this two-component developer and the replenishment developer.
[0161] The image forming apparatus used was a modified Canon color copier imageRUNNER ADVANCE C5560. A two-component developer was placed in each color developing device, a refill developer container containing a refill developer for each color was set, an image was formed, and various evaluations were performed before and after a paper feed durability test. For the paper feed durability test, a FFH output chart with an image ratio of 40% was used in a printing environment of 30°C temperature / 80% relative humidity (hereinafter referred to as "H / H"). FFH is a value that expresses 256 gradations in hexadecimal, with 00h being the 1st gradation (white background) of the 256 gradations and FFH being the 256th gradation (solid area) of the 256 gradations. The number of images output was changed depending on each evaluation item.
[0162] conditions: Paper: Laser beam printer paper CS-814 (81.4 g / m 2 ) (Canon Marketing Japan Inc.) It was modified to enable image formation speed of 80 (sheets / min) in full color on A4 size paper. Development conditions: The development contrast was made adjustable to any value, and the automatic correction by the main unit was not activated. The peak-to-peak voltage (Vpp) of the AC electric field was modified to a frequency of 2.0 kHz, and Vpp was modified to be variable in 0.1 kV increments from 0.7 kV to 1.8 kV. Each color was modified so that a monochrome image could be output.
[0163] The evaluation items are shown below. The evaluation results are shown in Table 6. For measurements with measurement error, the measurement was repeated a number of times until the measurement error was sufficiently small, and the arithmetic average value was used as the measurement value.
[0164] (1) Image Density After performing initial durability and durability image output evaluation (A4 landscape, 40% print ratio, 50,000 sheets) under H / H environment, a solid image (FFH) was output. Density was measured using a densitometer X-Rite404A (manufactured by X-Rite), and the average value of 6 points was taken as the image density. The difference in image density between the initial durability and durability image output was judged according to the following criteria. A: The difference in concentration is less than 0.10 B: The difference in density is 0.10 or more and less than 0.15 C: The difference in density is 0.15 or more and less than 0.20 D: The difference in concentration is 0.20 or more and less than 0.25 E: The difference in density is 0.20 or more and less than 0.30
[0165] (2) Toner scattering After initial durability and durability image output evaluation (A4 landscape, 40% print ratio, 50,000 sheets) were performed under H / H environment, the developing unit was removed from the main body, and the toner scattering status inside and outside the developing unit and the main body was visually inspected and evaluated according to the following criteria. A: No toner scattering B: Very slight toner scattering C: Slight toner scattering D: Toner scattering E: Serious toner scattering
[0166] (3) Coating resin abrasion resistance Under H / H environment, initial durability and durability image output evaluation (A4 landscape, 0% print ratio, 100,000 sheets) were performed. After that, the developer was removed from the main body, and 1 g of the developer or the developer before durability, 30 mL of distilled water, and 0.1 mL of Contaminon N described below were placed in a 100 mL flat-bottom glass beaker, and the operation of removing the supernatant after ultrasonic cleaning for 1 minute was repeated three times. Then, the obtained residue was dried in a dryer at 50 degrees for 24 hours to obtain a magnetic carrier sample. The resistivity of the obtained magnetic carrier sample was measured, and the rate of change in the measured value before and after the durability evaluation was judged in accordance with the following criteria. Contaminon N: A 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd. A: The decrease in resistivity due to durability is less than 5% compared to before durability B: The decrease in resistivity due to durability is 5% or more but less than 15% compared to before durability C: The decrease in resistivity due to durability is 15% or more but less than 30% compared to before durability D: The decrease in resistivity due to durability is 30% or more but less than 40% compared to before durability E: The resistivity after durability test is reduced by 40% or more compared to before durability test. The effects of the present invention were determined to be achieved when a product was rated A to C, which are equivalent to or better than existing technical products, for all of the above evaluation items (1) to (3).
[0167] <Examples 2 to 16 and Comparative Examples 1 to 5> Evaluation was carried out in the same manner as in Example 1, except that the magnetic carrier 1 was changed to one shown in Table 5. The evaluation results are shown in Table 6.
[0168] [Table 5]
[0169] [Table 6] [Explanation of symbols]
[0170] 1 Electrostatic latent image carrier 2 Charger 3 Exposure device 4. Developing Machine 5 Developing container 6 Developer carrier 7. Magnet 8 Regulatory Members 9 Intermediate transfer body 11 Transfer charger 12 Recording medium (transfer material) 13 Fixing unit 15. Cleaner 16 Pre-exposure means
Claims
1. A magnetic carrier comprising magnetic carrier particles having a magnetic core and a resin coating layer coating the surface of the magnetic core, The resin coating layer contains a resin A having a fluoropolymer portion and a resin B, The resin A has a first repeating structure represented by the following formula (8), 【Chemistry 1】 In the above formula (8), R 1 represents hydrogen or a methyl group. X 1 represents COO. R 2 represents an alkyl group having 1 to 20 carbon atoms; The alkyl group has some or all of its hydrogen atoms substituted with fluorine atoms, A part of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, The ratio of the number of fluorine atoms to the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group is 5.0 atomic % or more, and the ratio of halogen atoms other than fluorine atoms is 40 atomic % or less. The resin B has a third repeating structure represented by the following formula (10): 【Chemistry 2】 (R 5 represents hydrogen or a methyl group; R 6 represents a cyclohexyl group. The resin coating layer has an average thickness of 50 nm or more, The concentration of nitrogen atoms dN(x), the concentration of silicon atoms dSi(x), the concentration of fluorine atoms dF(x), the concentration of carbon atoms dC(x), the concentration of titanium atoms dTi(x), the concentration of strontium atoms dSr(x), the concentration of tin atoms dSn(x), the concentration of aluminum atoms dAl(x), and the concentration of oxygen atoms detected by X-ray photoelectron spectroscopy at a position of a depth of x nm from the surface of the magnetic carrier particle. When F(x) (atomic %) is defined as the ratio (dF(x) / [dN(x)+dSi(x)+dF(x)+dC(x)+dTi(x)+dSr(x)+dSn(x)+dAl(x)+dO(x)]) of the concentration of fluorine atoms dF(x) to the sum of dO(x) (dN(x)+dSi(x)+dF(x)+dC(x)+dTi(x)+dSr(x)+dSn(x)+dAl(x)+dO(x), F(0) satisfies the following formula (1), F(20) satisfies the following formula (2), A magnetic carrier characterized in that, when the x is an integer of 0 or more and 20 or less, the F(x) satisfies the following formula (3) for any x: 5.0≦F(0)≦15 (1) F(20)≦5.0...(2) |F(x+1)-F(x)|≦7.5...(3)
2. The concentration of nitrogen atoms dN(x), the concentration of silicon atoms dSi(x), the concentration of fluorine atoms dF(x), the concentration of carbon atoms dC(x), the concentration of titanium atoms dTi(x), the concentration of strontium atoms dSr(x), the concentration of tin atoms dSn(x), the concentration of aluminum atoms dAl(x), and the concentration of oxygen atoms detected by X-ray photoelectron spectroscopy at a position of a depth of x nm from the surface of the magnetic carrier particle When the ratio of the carbon atom concentration dC(x) (dC(x) / [dN(x)+dSi(x)+dF(x)+dC(x)+dTi(x)+dSr(x)+dSn(x)+dAl(x)+dO(x)]) to the sum of the carbon atom concentrations dO(x) (dN(x)+dSi(x)+dF(x)+dC(x)+dTi(x)+dSr(x)+dSn(x)+dAl(x)+dO(x)) is defined as C(x) (atomic %), F(0) / C(0) satisfies the following formula (4), F(20) / C(20) satisfies the following formula (5), 2. The magnetic carrier according to claim 1, wherein when x is an integer of 0 or more and 20 or less, F(x) and C(x) for any x satisfy the following formula (6): 0.060≦F(0) / C(0)≦0.30...(4) F(20) / C(20)≦0.060...(5) |F(x+1) / C(x+1)-F(x) / C(x)|≦0.15...(6)
3. The magnetic carrier according to claim 1 or 2, wherein the F(x) satisfies the following formula (7): F(10)≦8.0...(7)
4. 4. The magnetic carrier according to claim 1, wherein the resin A has a second repeating structure represented by the following formula (9): 【Chemistry 3】 (R 3 represents H or a methyl group. R 4 represents --O--. X 2 represents a hydrocarbon group having 1 to 12 carbon atoms.
5. The SP value of the second repeating structure is SPa 2 The SP value of the third repeat structure is SPb 3 When the above-mentioned SPa 2 and SPb 3 but, |SPa 2 -SPb 3 |≦2.5 The magnetic carrier according to claim 4, which satisfies the above.
6. A two-component developer containing a toner and a magnetic carrier, A two-component developer, wherein the magnetic carrier is the magnetic carrier according to any one of claims 1 to 5.
7. the electrostatic latent image carrier is charged, the electrostatic latent image forming step is to form an electrostatic latent image on the surface of the electrostatic latent image carrier, the electrostatic latent image is developed with a two-component developer in a developing device to form a toner image, the toner image is transferred to a transfer material with or without an intermediate transfer body, and the toner image is fixed to the transfer material, A replenishment developer for use in an image forming method in which the replenishment developer is replenished to a developing device in response to a reduction in a toner concentration of a two-component developer in the developing device, comprising: The replenishment developer contains a replenishment magnetic carrier and a toner, 6. A refill developer, comprising the refill magnetic carrier according to claim 1.
Citation Information
Patent Citations
Electrostatic image developing carrier
JP1988235963A
Negatively chargeable developer to be used for development of electrostatic charge image
JP1990168273A
Carrier for developing electrostatically charged image, and developer of electrostatically charged image
JP1997244303A
Electrifying member for development of electrostatic charge image and sleeve for development of electrostatic charge image
JP1998055109A
Electrostatic charge image developing carrier and developer
JP2001066826A